RESPONSIBILITY OF YOUTH IN THE IMPLEMENTATION OF IDEOLOGICAL SECURITY - Bobomurodov Erkin Khaitovich (Scholar Express Journal, 2023)
The article reveals the theoretical and practical importance of the formation and improvement of civil society among the youth of modern Uzbekistan, which serves as a continuation and an integral part of democratic transformations in society
Keywords: Prevention; ideology; ideological education